Visible and invisible bordering practices: The EU-African migration conundrum and spatial mobility of borders. Issue 4 (3rd October 2016) - Nshimbi, Christopher Changwe; Moyo, Inocent
Abstract : Purpose: Despite enacting numerous legislations, policies and practices accommodating third country nationals, Europe continues to erect a fortress against foreigners. The recent migration crisis on the shores of the Mediterranean seem to validate this view. As Europe searches for optimal solutions to the migration crisis, recent media and humanitarian organisation reports of surging African and Middle Eastern refugees and migrants bring into sharp focus and test these immigration measures. For this cause, the purpose of this paper is to interrogate European Union (EU)-Africa relationships on international migration issues. Design/methodology/approach: Located in the evolving field of border studies, the paper employs the concepts of displacement and humanitarianism in an effort to frame the EU-Africa relations on migration in the context of borders, boundaries and frontiers. A thorough review and critical analysis of relevant legislations, literature and media reports on the Africa-Europe migration interface is also conducted. Findings: The militarisation, securitisation, restrictive and, sometimes, draconian immigration regimes do not provide sustainable solutions to the migration crisis facing Europe. A rethinking around the integration and inclusion of immigrants into Europe's socioeconomic fabric, and addressing fundamental and structural weaknesses in EU-Africa relationships and respective economies is essential. Originality/value: Theoretically, the paper attempts to understand better, the way the EU and Africa engage each other on international migration issues, in the context of border studies. Empirically, the paper positions itself in policy engagements and the quest for practical solutions by the two continents in view of the migration crisis currently facing Europe.